1998
DOI: 10.1002/(sici)1096-8652(199804)57:4<338::aid-ajh12>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic thrombocytopenic purpura as presenting symptom of hepatitis C infection

Abstract: We report on 3 female patients with immunologic thrombocytopenic purpura (ITP) for whom diagnostic procedures evidenced a chronic Hepatitis C virus (HCV) infection. In 2 cases, a transfusion performed more than 10 years ago represented the probable way of contamination. One patient received a course of steroids, which normalized the platelet counts. Another one has been treated with repeated IV immunoglobulins, which induced partial responses of variable duration. HCV is responsible for many autoimmune manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 7 publications
4
21
1
2
Order By: Relevance
“…This association is particularly significant when compared with the prevalence of HCV in our age-matched healthy controls (0´4%). The clinical and laboratory data of our HCV-positive thrombocytopenic patients showed trends similar to those of most other reports of HCV-associated thrombocytopenia (Silva et al, 1992;Pawlotsky et al, 1995;Linares et al, 1996;Bauduer et al, 1998;Gerli et al, 1999). In our series, thrombocytopenia was the presenting manifestation of HCV infection in all cases.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This association is particularly significant when compared with the prevalence of HCV in our age-matched healthy controls (0´4%). The clinical and laboratory data of our HCV-positive thrombocytopenic patients showed trends similar to those of most other reports of HCV-associated thrombocytopenia (Silva et al, 1992;Pawlotsky et al, 1995;Linares et al, 1996;Bauduer et al, 1998;Gerli et al, 1999). In our series, thrombocytopenia was the presenting manifestation of HCV infection in all cases.…”
Section: Discussionsupporting
confidence: 90%
“…Several reports (Silva et al, 1992;Pawlotsky et al, 1995;Linares et al, 1996;Bauduer et al, 1998;Gerli et al, 1999), mostly from southern Europe, have shown an increased prevalence (5±35%) of hepatitis C virus (HCV) infection in patients with chronic acquired thrombocytopenia. The pathogenic mechanism of the thrombocytopenia in these patients has not been defined as symptoms of portal hypertension or splenomegaly were not evident in most of the cases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The various treatment modalities--including steroids, IV Igs, and splenectomy--have failed to achieve lasting responses. 2,3,23 IFN treatment has been investigated in isolated HCV-related thrombocytopenia in some studies, 2 of which have reported sustained improvement of thrombocytopenia, even in the first weeks of treatment, n,13 However, in the present case, thrombocytopenia improved in the first 4 weeks but was subsequently exacerbated. In addition, viral load failed to decrease by >2 logs.…”
Section: Discussionmentioning
confidence: 61%